Epistemologi Common Sense Abad XX - Abbas Hamami Mintaredja (Jurnal Filsafat "WISDOM", 2003)
The presence of G.E. Moore (1873-1956), undoubtedly has brought a new wave of thought. A thought that has changed the development of English philosophical thinking into analytic and neo realism. Moore has deconstructed Bradley's idealsm. Moore revived English philosophy of common sense. Common sense is a belief in direct apprehension of material things. It is important to solve daily life probelms. Common sense epistemology is specifically Moore epistemology. Is separates the subjects from objects distingtively. A subject sees factual objects in direct experience so that he gets sense data. To apprehend sense data directly, it involves conscious activity. The result of activity is the true and necessary knowledge. Common sense Moore's epistemology based on Aristotelian epistemology.Moore common sense epistemology influenced later philosophies of Russell and Ayer in English, and Ayn Rand in America. Russell perceived common sense as an inderence rule to daily experience based on istinct. It differed from Ayer who developed his philosophy based on verification. Common sense is an understanding to given object that is directly observed. Ayn Rand in America developed his epistemology based on objective object as a real material things. The truth of knowledge is apriori. Its based on truism like Moore's epistemology.